Dermatoanthropology of Ethnic Skin and Hair - Vashi, Neelam A.; Maibach, Howard I. (Springer International Publishing : Imprint: Springer, 2017)
Dermatoanthropology of Ethnic Skin and Hair is a comprehensive text that extensively examines cutaneous disease in persons with skin of color. The breadth of knowledge in this book encompasses the wide scope of dermatologic disease with 26 distinct and unique chapters. It serves as a guide to the diagnosis and treatment of skin disorders for those populations with darker skin types. Vashi and Maibach's Dermatoanthropology of Ethnic Skin and Hair provides an overview of medical, surgical, and cosmetic dermatology in addition to providing an extensive anthropological and basic science background to fully understand skin disorders in persons of color. Topics of discussion include anthropology of skin and hair, biophysical properties of ethnic skin, structure and function of the skin, physiologic pigmentation, mucosal lesions, acne, rosacea, inflammatory disorders, infections, autoimmune disorders, connective tissue disease, hyperpigmentation, hypopigmentation and depigmentation, keloids, scarring, pediatric disease, alopecias, adnexal disorders, common cosmetic concerns and treatments, and cultural considerations.
Keywords: Medicine.; Dermatology.; elektronické knihy; electronic books